PENGARUH KONSENTRASI ASAM GIBERELAT (GA ) DAN LAMA PERENDAMAN TERHADAP VIABILITAS, VIGOR dan 3 PERTUMBUHAN BENIH JARAK (Jatropha curcas L.) KLON IP-1P di PEMBENIHAN - Asep Samsul Mustopa (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2015)
The experiment was carried out at Plant Biotechnology laboratorium and experimentalfield Faculty of Agriculture University of Winaya Mukti Tanjungsari Sumedang which the altitude is about 850 meters above sea level, from March 2008 until May 2008.Theobjective of this experiment was to studying the interaction effect of giberellat acidconcentration and and soaking time on seed viability, seed vigor, growth and yield ofJatropha curcas in nursery.Design used was Randomized Block Design (RBD) withfactorial pattern, treatment consisted of two factors and two replications. The first factorwas giberellat acid (GA3) concentration (K) which consisted of 4 levels namely : k1=250 ppm, k2= 500 ppm, k3= 750 ppm and k4= 1000 ppm. The second factor soakingtime on GA34 (M) which consisted of 4 levels namely : m1= 6 hour, m2= 18 hour dan m = 24 hour.The results of these experiment showed there was aninteraction between giberellat acid concentration and and soaking time on high of plant20 day after planting (DAP), 40 DAP, 60 DAP, number of leaves 20 DAP, 40 DAP, 60DAP, length of root, number of root, dry wight of root and dry wight of shoot.